Experimental study of the influence of different weir types on the rate of air entrainment - Emiroglu, ME; Baylar, A (Canadian Assoc Water Quality, 2003)
Aeration is used in water treatment to alter the concentration of dissolved gases, to strip volatile organics, and to reduce tastes and odours. This can be obtained by creating turbulence in the water. One method of producing such turbulence is via the overflow jets downstream of weir structures. This paper investigates the effect of varying weir types on the air entrainment rate. Empirical correlations predicting the maximum penetration depth and air entrainment rate were developed for different weir types. It is demonstrated that the air entrainment rate of the broad-crested weirs is generally much better than for the sharp-crested weir and the labyrinth weirs. The air entrainment rate increased as the weir longitudinal slope of the broad-crested weirs and the weir sill slope of the labyrinth weirs became larger.
Keywords: entrainment; aeration; weir; penetration depth; water jet expansion